PENGEMBANGAN MEDIA WEBSITE DAN CD INTERAKTIF BERBASISSEJARAH SEBAGAI UPAYA PENINGKATAN PENGETAHUAN WISATASEJARAH SITUS PURBAKALA DI GUNUNGKIDUL - AnggaritaWahyuningsih, dan M. Saepudin Wahab, Eko Yuliyanto, Friyatmoko Wahyu Kusumo, Arif Hidayat, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
Gunungkidul saves the potential that other regions have never had, that is ancientsites. This condition makes this region as the rich archeological area. However, theinformation on these ancient sites are difficult to be found by tourists. This aim ofresearch is to create the website and interactive CD on the ancient sites in Guinungkidul.This research is qualitative descriptive. The Data were taken from Gunungkidulsub-districts that have prehistoric monument, such as sites, cave, and lumping batu. Thecollection of the data was done by having 1) interview, 2) observation, 3) literaturestudy, 4) data validity, 5) reduction, 6) data display, deduction and verification.This research has produced an interactive CD and website that include theinformation on Rancang Kencana Cave, Bleberan Site, Lumpang dan Lesung Batu,Sokoliman Site, Braholo Cave, Song Tritis, Lawa Cave, Song Gilap, Menhir Semanu Kidul,Cenguk Cave, Gunung Bang Site, Gondang Site, and Song Bentar.Keyword: History tour, Gunungkidul, Interactive CD, Website